Ferulic Acid Esterase-Producing Lactobacilli as Silage Inoculants: A Review on the Efficacy of Improving Fiber Composition and Digestibility of Forages - Estefanía Andrada; María Claudia Abeijón-Mukdsi; Gabriel Vinderola; Roxana Beatriz Medina (Fermentation)
Environmental-, animal-, and plant-associated factors are involved in the intake and digestibility of forages. Ferulated crosslinks are key targets for increasing the extent of fiber digestion in forages, for which ferulic acid esterase-producing lactic acid bacteria (FAE+ LAB) arise as silage inoculants that could beneficially impact animal husbandry. In this review article, we analyze the published effects of these inoculants on silage fiber composition, digestibility measures, ferulic acid content, and animal performance. To date, 17 FAE+ LAB strains have been evaluated in ensiling trials, obtaining variable results. When significant effects were detected, reductions in the content of neutral or acid detergent fiber (1.3–6.6% DM, compared with uninoculated silages) and increased digestibility measures (1.4–9.6% DM) were the most frequent outcomes. FAE+ LAB increased the free FA content of silages in several reports. Factors involved in the variability of responses have been scarcely evaluated but include inoculant strain, strain–forage combination, forage characteristics, and ensiling conditions. Two studies indicate that productive and health improvements were obtained when FAE+ LAB-inoculated silages were predominant in the diet of growing steers or dairy goats. Additional research is needed to understand the factors associated with the performance of FAE+ inoculants and the extent of their potential benefits for animal nutrition.